(untitled) (Docentes 2.0 Journal, 2019)
Due to the fact that San Marcos University is a leader in technology-assisted education in Costa Rica, it is important to extend the learning curve obtained in the virtual education into the in-person one, in order to achieve a virtuous circle than enriches the teaching strategies. Mainly, it has been promoted the usage of a methodology in which the instructor introduces contents by using multimedia and audiovisual learning objects, allowing the achievement of the learning objectives proposed efficiently and the academic quality assurance. San Marcos University has successfully achieved the successful implementation of a LMS platform, as an exponential resource in the teaching of face-to-face education, showing the improvement in the techno-pedagogical competencies of instructors and, at the same time, getting rid of the uncertainty that the use of a virtual platform generates, and reducing technophobia in the students by increasing the approach to virtual environments. Currently the use of a virtual platform in face-to-face course has allowed to keep record of the instructors that use it with a specific purpose, under the identification of the three levels of the use of collaborative resources. From the first level that is used to upload some learning objects, up to a third level in which a virtual course has been created or reused in particular, with the application of didactic techniques to interact in class or as a support to the flipped classroom methodology. This usage of the platform allows the development of a university culture promoting integrated learning-teaching, quality, and state-of-the-art didactic methodologies and techniques based on virtual environments. Besides, it helps to achieve the goals of the University to become a zero-paper institution, through digitalization.